The Influence of Profitability, Solvency, Institutional Ownership, and Investment Decisions on Company Value - Yesinta Febriati; Rina Mudjiyanti; Suryo Budi Santoso; Hadi Pramono (Innovation Business Management and Accounting Journal, 2024)
This research aims to obtain empirical evidence regarding the variables profitability, solvency, institutional ownership, and investment decisions on company value. This research method uses quantitative methods. The population in this research are companies listed on the Jakarta Islamic Index 70 for the 2020-2023 period. The data used is secondary data sourced from the official website of the Indonesian stock exchange and the company's official website. The sampling technique in this research used the purposive sampling method. The quality of the samples that met the criteria was 218 samples. The results of this study show that solvency, institutional ownership, and investment decisions have a positive effect on company value, while profitability has no effect on company value in companies listed on the Jakarta Islamic Index 70 for the 2020-2023 period. These findings provide valuable insights for investors, policymakers, and corporate managers seeking to enhance company value.